ANALYSIS OF IPO UNDERPRICING FLUCTUATION: EMPIRICAL STUDY IN INDONESIA STOCK EXCHANGE - Hanafi, Mamduh M. (Jurnal Dinamika Manajemen, 2016)
This study attempts to analyze fluctuation of IPO underpricing in Indonesia market from 1990-2010. This research test three proposed hypotheses: changing risk composition, changing incentives alignment, and changing issuersâ objective function. The researcher also add other variables as potential explanation for underpricing fluctuation: introduction of book building mechanism in year 2000, industry (finance and non-finance), market return, and privatization (IPO of state owned companies and non-state owned companies). The analysis shows that market return and the introduction of book building mechanism have positive impact on underpricing. However, when both variables in regression equation are included, the effect of market return disappears, while the effect of book building mechanism persists. This finding seems to support Book Building advantage arguments and changing issuersâ objective functions hypothesis, in the sense that the introduction of book building mechanism changes objective function of parties involved. Final result is a change in IPO under pricing.